Institutional contexts of sustainable agriculture in three agro-ecological zones in a district in West-Central Nepal a sociological analysis - Gurung, Jit B.; Bonifacio, Manuel F. (Quezon City College of Social Sciences and Philosophy, University of the Philippines Diliman, 1996)
Based on multiple triangulation strategy, this study analysed sustainable agriculture in three agro-ecological and ethnic belts in west-central Nepal by taking into consideration the institutional variables of caste/ethnicity, class and gender and their manifestations in attitudes, worldviews (fatalism) and interpersonal communication patterns in the context of sustainable agriculture. Sustainability was conceptualized along three major discussions comprising food sufficiency, environmental stewardship, and community.
Thesis (Doctor of Philosophy in Sociology)--University of the Philippines Diliman
Keywords: Sustainable agriculture; Sustainable agriculture -- Asia -- Congresses